Overproduction of large VLDL particles is driven by increased liver fat content in man - Adiels, M; Taskinen, M.-R; Packard, C; Caslake, M. J; Soro-Paavonen, A; Westerbacka, J; Vehkavaara, S; Häkkinen, A; Olofsson, S.-O; Yki-Järvinen, H; Borén, J (Diabetologia, 2006)
Aims/hypothesis We determined whether hepatic fat content and plasma adiponectin concentration regulate VLDL₁ production. Methods A multicompartment model was used to simultaneously determine the kinetic parameters of triglycerides (TGs) and apolipoprotein B (ApoB) in VLDL₁ and VLDL₂ after a bolus of [²H₃]leucine and [²H₅]glycerol in ten men with type 2 diabetes and in 18 non-diabetic men. Liver fat content was determined by proton spectroscopy and intra-abdominal fat content by MRI. Results Univariate regression analysis showed that liver fat content, intra-abdominal fat volume, plasma glucose, insulin and HOMA-IR (homeostasis model assessment of insulin resistance) correlated with VLDL₁ TG and ApoB production. However, only liver fat and plasma glucose were significant in multiple regression models, emphasising the critical role of substrate fluxes and lipid availability in the liver as the driving force for overproduction of VLDL₁ in subjects with type 2 diabetes. Despite negative correlations with fasting TG levels, liver fat content, and VLDL₁ TG and ApoB pool sizes, adiponectin was not linked to VLDL₁ TG or ApoB production and thus was not a predictor of VLDL₁ production. However, adiponectin correlated negatively with the removal rates of VLDL₁ TG and ApoB. Conclusions/interpretation We propose that the metabolic effect of insulin resistance, partly mediated by depressed plasma adiponectin levels, increases fatty acid flux from adipose tissue to the liver and induces the accumulation of fat in the liver. Elevated plasma glucose can further increase hepatic fat content through multiple pathways, resulting in overproduction of VLDL₁ particles and leading to the characteristic dyslipidaemia associated with type 2 diabetes.